Virtual Reality experiments in the field - Maria Alejandra Quirós-Ramírez; Anna Feineisen; Stephan Streuber; Ulf-Dietrich Reips (PLoS ONE, 2025)
Virtual Reality (VR) has paved its way into experimental psychology due to its capacity to realistically simulate real-world experiences in a controlled way. Theoretically, this technology opens the possibility to conduct experiments anywhere in the world using consumer hardware (e.g. mobile-VR). This would allow researchers to access large scale, heterogeneous samples and to conduct experiments in the field in cases where social distancing is required – e.g. during the COVID-19 pandemic. Here, we investigate the feasibility of carrying VR experiments in the field using mobile-VR through a stress inductive (public speaking task) and a relaxation (nature) task and contrast them with results in the laboratory (HTC Vive and mobile-VR). The first experiment employed a 2 (device: HTC Vive Pro (HMD) versus Wearality Sky VR smartphone adapter) x 3 (audience: ‘none’, ‘attentive’, ‘inattentive’) between-subjects design. Thirty-four participants took part in the experiment and completed a public speaking task. No significant difference was detected in participants’ sense of presence, cybersickness, or stress levels. In the second experiment, using an inexpensive Google Cardboard smartphone adapter a 3 (between: device setting) x 2 (within: task) mixed-design was employed. Sixty participants joined the experiment, and completed a public speaking and a nature observation task. No significant difference in participants’ sense of presence, cybersickness, perceived stress and relaxation were detected. Taken together, our results provide initial evidence supporting the feasibility and validity of using mobile VR in specific psychological field experiments, such as stress induction and relaxation tasks, conducted in the field. We discuss challenges and concrete recommendations for using VR in field experiments. Future research is needed to evaluate its applicability across a broader range of experimental paradigms.